PELATIHAN SIMPLE TENSE UNTUK MENUNJANG KEMAMPUAN PERCAKAPAN SEHARI-HARI DAN PERKEMBANGAN BAHASA INGGRIS ANAK DI KELOMPOK MAJLIS TAKLIM AL FATTAH SERPONG TERRACE - Haryati Haryati; Diyah Iis Andriyani; Rizky Tazkiyatul Ummami (Universiitas Pamulang, 2023)
ABSTRACT The purpose of this Community Service activity is to help parents to acquire the ability to speak English in different context tenses and help children with English assignments. PkM activities take place at Majlis Taklim Al-Fattah which is located in Serpong Terrace in South Tangerang; participants are members of associations in religious activities. There were 25 participants who had difficulties in helping children complete English assignments related to English grammar and the desire to speak English. The method to be applied is qualitative which is directed at elaborating the PkM results which are descriptive in nature. After the training process, we found two positive points, namely participants were able to recount their daily activities, past activities, and plans they would do in a short and correct way. They are able to arrange randomly arranged sentences into correct sentences according to the context they have studied. In addition, the results of the questionnaire show that parents are able to help their children's schoolwork in terms of grammar such as present and future tense. In the present simple, parents still have difficulty in distinguishing between -s and -es affixes. The rest, for the past simple, parents do not show significant ability due to the weakness of identifying the first and second verbs. Keywords: grammar, English children acquisition, speaking